From health advice to taboo: community perspectives on the treatment of sleeping sickness in the Democratic Republic of Congo, a qualitative study. - Alain Mpanya; David Hendrickx; Sylvain Baloji; Crispin Lumbala; Raquel Inocêncio da Luz; Marleen Boelaert; Pascal Lutumba (Public Library of Science (PLoS), 2015)
BACKGROUND:Socio-cultural and economic factors constitute real barriers for uptake of screening and treatment of Human African Trypanosomiasis (HAT) in the Democratic Republic of Congo (DRC). Better understanding and addressing these barriers may enhance the effectiveness of HAT control. METHODS:We performed a qualitative study consisting of semi-structured interviews and focus group discussions in the Bandundu and Kasaï Oriental provinces, two provinces lagging behind in the HAT elimination effort. Our study population included current and former HAT patients, as well as healthcare providers and program managers of the national HAT control program. All interviews and discussions were voice recorded on a digital device and data were analysed with the ATLAS.ti software. FINDINGS:Health workers and community members quoted a number of prohibitions that have to be respected for six months after HAT treatment: no work, no sexual intercourse, no hot food, not walking in the sun. Violating these restrictions is believed to cause serious, and sometimes deadly, complications. These strong prohibitions are well-known by the community and lead some people to avoid HAT screening campaigns, for fear of having to observe such taboos in case of diagnosis. DISCUSSION:The restrictions originally aimed to mitigate the severe adverse effects of the melarsoprol regimen, but are not evidence-based and became obsolete with the new safer drugs. Correct health information regarding HAT treatment is essential. Health providers should address the perspective of the community in a constant dialogue to keep abreast of unintended transformations of meaning.